A (in)efetividade da outorga de direito de uso dos recursos hídricos: um estudo no sistema hídrico engenheiro ávidos, São Gonçalo e rio Piranhas, sertão Paraibano - Bandeira, Romeu Tavares (2022)
Water is an environmental good essential to the life of both people and other living beings, even though its availability is irregular along the earth's surface, reason why it is characterized as a finite resource that needs good management. In this regard, the National Water Resources Policy (PNRH) lists a series of guiding instruments for carrying out this management, such as granting of the right to use water resources, the object of study of this dissertation. On this matter, the research problem is verified in the contrast between what is duly affirmed in the national legal mechanisms on the need to grant the right to use water resources and what is visualized in the (in)effectiveness of the instrument in order to identify possible obstacles to be overcome. Thus, the following questions focus on this problem: does the granting of the right to use water resources oppose the right to access to water? At the legal level, is it an effective instrument to control the multiple uses of water? Therefore, the general objective is to analyze the instrument for granting the right to use water resources as an essential element to the exercise of the right to access to water. Meanwhile, the specific objectives of this work are: a) to point out the characteristics of the right to access to water in the national legal system and its relationship with the right to development; b) describe the normative treatment of the granting of the right to use water resources; c) carry out the study and data collection of grants in the Engenheiro Ávidos, São Gonçalo and Rio Piranhas water system. In order to analyze the (in)effectiveness of this instrument and the mitigation of the right to access to water resulting from it, it was decided to select a specific study area, which is the water system that belongs to the Alto Piranhas sub-basin, inserted in the Hydrographic Basin Piranhas-Açu (BHPA), located in the semiarid region of Paraiba, which, due to its climatic, geological and management characteristics, suffers from water scarcity. It is worth noting that the time period for collecting data from the grants granted in the study area is from January 2013 to December 2021 and they are available in the ANA (National Water and Basic Sanitation Agency) and AESA (Executive Agency of Water Management in Paraíba) databases. Furthermore, the approach used is deductive reasoning and the research is qualitative-quantitative, based on a bibliographic and documental review of an exploratory nature and with descriptive data analysis. At the same time, the present study is based on conducting field research. Regarding the legislation, the Federal Constitution of 1988, Law No. 9,433/1997, State Decree No. 19,260/97, ANA Resolution No. 1,938/2017 and ANA/AESA Joint Resolution No. 76/2018 are studied. Therefore, it starts from the hypothesis that the grant instrument enables the multiple uses of water, which is why it is an essential element in the exercise of the right to access to water. In conclusion, it is believed that this dissertation will be able to contribute to the water management institutions, notably within the State of Paraíba, by identifying obstacles to the achievement of the right to access to water related to the granting of the right to use water resources and, in light of this context, the essentiality of this study can be seen due to its scientific relevance and its innovative character.